Singular features of trypanosomatids' phosphotransferases involved in cell energy management - Pereira, Claudio Alejandro (2011)
Trypanosomatids are responsible for economically important veterinary affections and severe human diseases. In Africa, Trypanosoma brucei causes sleeping sickness or African trypanosomiasis, while in America, Trypanosoma cruzi is the etiological agent of Chagas disease. These parasites have complex life cycles which involve a wide variety of environments with very different compositions, physicochemical properties, and availability of metabolites. As the environment changes there is a need to maintain the nucleoside homeostasis, requiring a quick and regulated response. Most of the enzymes required for energy management are phosphotransferases. These enzymes present a nitrogenous group or a phosphate as acceptors, and the most clear examples are arginine kinase, nucleoside diphosphate kinase, and adenylate kinase. Trypanosoma and Leishmania have the largest number of phosphotransferase isoforms ever found in a single cell; some of them are absent in mammals, suggesting that these enzymes are required in many cellular compartments associated to different biological processes. The presence of such number of phosphotransferases support the hypothesis of the existence of an intracellular enzymatic phosphotransfer network that communicates the spatially separated intracellular ATP consumption and production processes. All these unique features make phosphotransferases a promising start point for rational drug design for the treatment of human trypanosomiasis. © 2011 Claudio A. Pereira et al.